2002
DOI: 10.1097/00005537-200212000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy in Head and Neck Squamous Cell Carcinoma

Abstract: Sentinel lymph node biopsy is technically feasible and is a promising, minimally invasive method for staging the regional lymphatics in patients with stage N0 HNSCC. Lymphoscintigraphy alone may determine the levels that require treatment in patients with disrupted or previously operated cervical lymphatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 43 publications
3
39
0
2
Order By: Relevance
“…Taylor et al 20 reported an SN identification rate of 89% at lymphoscintigraphy in nine patients with T2N0 oral or oropharyngeal cancer Another study by Mozilla et al 23 showed SN visualization in 95% of 41 patients. Pitman et al 27 also demonstrated a 95% identification rate in 20 patients with oral cancer. On the other hand, Koch et al 14 identified SNs at lymphoscintigraphy with use of radiolabeled colloid alone in only two of five patients with SCC in the oral cavity.…”
Section: Discussionmentioning
confidence: 92%
“…Taylor et al 20 reported an SN identification rate of 89% at lymphoscintigraphy in nine patients with T2N0 oral or oropharyngeal cancer Another study by Mozilla et al 23 showed SN visualization in 95% of 41 patients. Pitman et al 27 also demonstrated a 95% identification rate in 20 patients with oral cancer. On the other hand, Koch et al 14 identified SNs at lymphoscintigraphy with use of radiolabeled colloid alone in only two of five patients with SCC in the oral cavity.…”
Section: Discussionmentioning
confidence: 92%
“…The accuracy of the technique is, however, reported as 90% to 100% in most of these small series. [4][5][6][7] Data collected from 22 centers were reported at the first international conference on SNB in HNSCC. 8 The conclusion was that SNB is an accurate technique in centers that performed more than 10 cases of SNB.…”
mentioning
confidence: 99%
“…They amended the study after initial 9 cases and included patients with clinically positive neck nodes. Still, no blue lymphatic channels or node were visualized after injection of 1 % isosulfan blue dye [13].…”
Section: Discussionmentioning
confidence: 92%